PERAN LAPORAN KEUANGAN SEDERHANA DALAM RUMAH TANGGA - Rakhmawati Oktavianna; Benarda Benarda; Sevty Wahiddirani Saputri; Purwatiningsih Purwatiningsih; Sri Nitta Crissiana Wirya Atmaja (Abdimisi, 2021)
The Community Service Program provided is a way of making simple financial statements for PKK women in Ciater Village, which aims to prepare PKK women in Ciater Serpong Village to be able to independently record family finances effectively and efficiently. In addition, the participating mothers will be able to manage and plan finances in their household effectively and efficiently. The target of this service is all PKK women, residents of Ciater Serpong Village, most of whom still do not understand in managing finances and doing simple financial reporting in their households. By being given explanations and training on how to manage finances to make simple financial reports, the participants were enthusiastic about participating in PKM. The results of this PKM proved that women in Ciater Village could master how to make simple financial reports quickly and well and increase their determination and concern for financial records in their respective families. So that mothers can manage household expenses and financial planning well.